Avaliação da Taxa de Exposição em Exames Radiológicos Realizados em Procedimentos Cirúrgicos - Minimização dos Riscos em Indivíduos Ocupacionalmente Expostos - Branco, Isabela Soares Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This paper consists in the evaluation of the exposure rate to ionizing radiation to which professionals working in surgical procedures which require radiological examinations are subjected. Were initially performed real-time readings of exposure rate within four distinct operating rooms during the execution of four surgical procedures that made use of fluoroscopy equipment (including three orthopedic surgeries, one in the shoulder, one in the arm, another for deployment of metal pin in the leg region, and a fourth for vascular procedure); in these surgeries were used ionization chamber detector and an electrometer. In order to check the values achieved, was made a re-evaluation of the distribution of the rate of exposure to radiation, from the surgical procedures, now with thermoluminescent dosimeters (TLDs). For this, thirty TLDs were distributed in the operating rooms, arranged in points of interest as occupation by professionals. The TLDs were prepared for thirty consecutive days, after which they were removed and replaced with new dosimeters not exposed yet. The dosimeters were subjected to reading of the rate of exposure; this procedure was repeated for four months without interruption. The quantification of the results sought primarily to convert the rate of exposure for equivalent dose rate, both in measurements with ionization chamber as in measurements with TLDs, in order to highlight the presence of the biological effect of ionizing radiation for comparisons within scientific context. Then, the results were plotted to establish the relationship between the values of equivalent dose and the distance to the central axis of the x -ray source, confirming the inverse square law for distance. Finally, the values were associated with the maximum limit recommended by the legislation for occupationally exposed individuals. The methodology for the analysis and quantification of the data in this work aims at implementing a work plan that meets ...

O trabalho consistiu na avaliação da taxa de exposição à radiação ionizante à qual são submetidos os profissionais que atuam nos procedimentos cirúrgicos, e que necessitam da realização de exames radiológicos. Inicialmente foram realizadas leituras em tempo real da taxa de exposição no interior de quatro salas de cirurgia distintas, durante a execução de quatro procedimentos cirúrgicos que fizeram uso de equipamento de fluoroscopia (sendo três cirurgias ortopédicas, uma na região do ombro, uma no braço, outra para implantação de pino metálico na região da perna, e uma quarta para procedimento vascular), nestas cirurgias, foram utilizados um detector do tipo câmara de ionização e um eletrômetro. De modo a aferir os valores obtidos, foi realizada novamente a avaliação da distribuição da taxa de exposição à radiação, provenientes dos procedimentos cirúrgicos, agora utilizando dosímetros termoluminescentes (TLD's). Para isto, foram distribuídos trinta TLD's nas salas de cirurgia, dispostos em pontos de interesse conforme ocupação pelos profissionais do Setor. Os TLD's ficaram dispostos por trinta dias consecutivos, após o que eram retirados e substituídos por novos dosímetros ainda não expostos. Os dosímetros foram submetidos à leitura da taxa de exposição, esse procedimento se repetiu por quatro meses ininterruptamente. A quantificação dos resultados requereu primeiramente a conversão dos valores de taxa de exposição para taxa de dose equivalente, tanto nas medições utilizando câmara de ionização quanto nas medições com os TLD's, a fim de evidenciar a presença do efeito biológico da radiação ionizante para comparações no âmbito científico. Em seguida, os resultados compuseram gráficos onde estabeleceu-se a relação entre os valores obtidos de dose equivalente e a distância das medidas com relação ao eixo central da fonte de raios-x, confirmando ...
Assessment Exposure Rate in Radiological Examinations done in Surgical Procedures - Minimizing Risk in Occupationally Exposed Individuals
Keywords: Exposição ocupacional; Doenças profissionais; Exposição a radiação; Radiometria; Radiation Exposure